198k views
0 votes
If h(x)=-2x+1. find h(3)+7
1-0
2-1
3-2
4-3​

User Mrateb
by
5.9k points

2 Answers

3 votes
h(3) = -2(3) +1 = -5
h(3) + 7 = 2
User Uri Shalit
by
6.2k points
5 votes

Answer:

3. -2

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

h(x) = -2x + 1

h(3) is x = 3

Step 2: Evaluate

  1. Substitute in x: h(3) + 3 = [-2(3) + 1] + 3
  2. Multiply: h(3) + 3 = [-6 + 1] + 3
  3. Add: h(3) + 3 = -5 + 3
  4. Add: h(3) + 3 = -2
User Robert Hui
by
6.2k points